(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3CeQ GdJhGHjf hNHQge HYjf GdhQOI , hgj QCS GdYjf ef GdLRjQI (B: (3MOKfi YHGS Hf gTGe hCHi eNfa bGdhG (B: (3deG aQZ eQhGf ef eQL QGgW bUO eUQ s
(3BNQgG (B:s
(3jJab BNQgG eY BNQ GdLRA GdSGOS ef GdfSNI GdChdi JeGekG s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs